Brain-Computer Interface based on EEG signals - Marek, Leszek; Plechawska-Wójcik , Małgorzata (Journal of Computer Sciences Institute, 2016)
The aim of the article is to test the brain-computer interface application using the SSVEP paradigm. During the realization of the project various methods of recording brain activity were tested, and the suitable acquisition device was chosen. Consecutive stages of the interface operation, which are data processing and classification, were presented in the OpenVibe environment. Finally, the usefulness and efficiency were estimated using a designed application.